Salmonella outer membrane vesicles displaying high densities of pneumococcal antigen at the surface offer protection against colonization. Issue 17 (21st April 2015) - Kuipers, Kirsten; Daleke-Schermerhorn, Maria H.; Jong, Wouter S.P.; ten Hagen-Jongman, Corinne M.; van Opzeeland, Fred; Simonetti, Elles; Luirink, Joen; de Jonge, Marien I.
Abstract: Bacterial outer membrane vesicles (OMVs) are attractive vaccine formulations because they have intrinsic immunostimulatory properties. In principle, heterologous antigens incorporated into OMVs will elicit specific immune responses, especially if presented at the vesicle surface and thus optimally exposed to the immune system. In this study, we explored the feasibility of our recently developed autotransporter Hbp platform, designed to efficiently and simultaneously display multiple antigens at the surface of bacterial OMVs, for vaccine development. Using two Streptococcus pneumoniae proteins as model antigens, we showed that intranasally administered Salmonella OMVs displaying high levels of antigens at the surface induced strong protection in a murine model of pneumococcal colonization, without the need for a mucosal adjuvant. Importantly, reduction in bacterial recovery from the nasal cavity was correlated with local production of antigen-specific IL-17A. Furthermore, the protective efficacy and the production of antigen-specific IL-17A, and local and systemic IgGs, were all improved at increased concentrations of the displayed antigen. This discovery highlights the importance of an adequate antigen expression system for development of recombinant OMV vaccines. In conclusion, our findings demonstrate the suitability of the Hbp platform for development of a new generation of OMV vaccines, and illustrate the potential of using this approach to develop a broadly protective mucosal pneumococcal vaccine.